Cognitive flexibility's role in shaping self-perception of aging, body appreciation, and self-efficacy among community-dwelling older women - Mona Metwally El-Sayed; Manal Mohammed Hawash; Mahmoud Abdelwahab Khedr; Sarah Ali Hafez; El-Saied; Samir Abdelnaby Essa; Sameer Mohammed Sayyd; Ayman Mohamed El-Ashry (BMC, 2024)
Abstract Background Cognitive flexibility, the capacity to adjust to new information, affects how aging is perceived. In Egyptian culture, older women's views on aging are shaped by societal gender roles and expectations. These views influence their body image and belief in their abilities, all melded by cultural standards and values. Aim Investigate the mediating role of cognitive flexibility in the relationship between self-aging perception, body appreciation, and self-efficacy among community-dwelling older women. Methods A correlational analytical design was used on 200 women aged 60 years or older using the Cognitive Flexibility Inventory, Self-Perceptions of Aging, General Self-Efficacy Scale, and Body Appreciation Scales. Structural equation modeling was used in the analysis. Results The study found that cognitive flexibility is positively related to self-perception of aging and body appreciation and is also significantly related to general self-efficacy. However, no significant relationship was found between body appreciation and general self-efficacy. Additionally, the study found that cognitive flexibility partially mediates the relationship between self-perception of aging and body appreciation and fully mediates the relationship between body appreciation and self-efficacy. Conclusion Cognitive flexibility is vital in the relationships between self-perceptions of aging, body appreciation, and self-efficacy among older women. Therefore, nursing interventions targeting cognitive flexibility are recommended to promote positive self-aging perceptions, body appreciation, and self-efficacy in this population.